Description of complaints/clinical symptoms and examination results of the SARS-CoV-2 rapid test in Brata Medika Laboratory Clinic Pare - Kediri in February 2021 - Acivrida Mega Charisma; Arif Rahman Nurdianto; Rizal Fauzi Nurdianto; Fery Setiawan; Heribertus Agustinus Tena (Universitas Muhammadiyah Surabaya, 2022)
SARS-CoV-2 antigen rapid test is one of the examinations widely used for early detection of Covid-19 infection. Rapid test is considered to have more advantages, is faster, and is cheaper than molecular PCR testing, and more accurate than rapid antibody tests. Its weakness is especially in detecting samples with small quantities of the virus. The study was conducted using a retrospective method. The data was taken from the patient's medical record of the SARS -CoV-2 antigen rapid swab test at Brata Medika Pare Clinical Laboratory for the period of February 2021. Data inclusion criteria including the examination, complete identity, results of anamnesis examination and rapid test examinations. Data were analyzed in a tabular form containing frequency and percentage. There were 18 (22.5%) patients with positive SARS-CoV-2antigen rapid swab test results, 16 (89%) with complaints/symptoms, and 2 (11%) without complaints/symptoms. Meanwhile, 62 (77.5%) were found with negative SARS-CoV-2 antigen rapid swab test results where 18 (29.0%) were patients with complaints/symptoms and 44 (71.0%) were patients without complaints/symptoms. The high percentage of negative SARS-CoV-2 antigen rapid swab test results in patients with complaints/symptoms (29.0%), it is recommended that a confirmatory examination with the molecular PCR test be carried out.